KEBIJAKAN PEMERINTAH BHUTAN DALAM PEMBERDAYAAN SEKTOR PARIWISATA UNTUK MEMASUKI SAFTA (SOUTH ASIAN FREE TRADE AREA) TAHUN 2002-2007 - Azela, Rizki; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the Government Policies In Empowerment Bhutan TourismSector to Enter SAFTA (South Asian Free Trade Area) 2002-2007. Bhutan's tourism industrybegan in 1974 It was introduced with the main objective to increase revenue, especiallyforeign exchange and publish unique culture and traditions of the country to the outsideworld, and contribute to socio-economic development of the country. In the tourism sector,tourism policy of Bhutan also developed in accordance with the principle of "high value lowimpact".Bhutan tourism development experience a variety of problems, challenges andobstacles that national and global scale. There should also be a change of paradigm inlooking at tourism in the context of national development.The research method used is a descriptive of qualitative research method about thefacts. This research is an explanatory that describe about problem, indication, policies, andactions. In writing techniques, the author’s collect and collate data through library researchfrom several sources like books, journals, articles, websites, the media and others. Theauthor’s also use decision making theory and the theory of comparative advantage.This research shows Bhutan's development philosophy is based on GNH has becomethe principle for socio-economic development of Bhutan. The concept of GNH defines Bhutandevelopment goals as improvement in the happiness and satisfaction of the people better thanthe growth of Gross National Product (GNP). GNH has become the overall developmentphilosophy of Bhutan as a concept has guided the country's development policies andprograms.Keywords: Policy, GNH, Development, Sustainable of Tourism.